EFL LEARNERS’ ABILITY IN ANSWERING STRUCTURE AND WRITTEN EXPRESSION SECTION ON TOEFL PREDICTION TEST - Alfatra Fadeni; Yuli Herman; Risza Dwiputri (Universitas Mahaputra Muhammad Yamin, 2026)
This study examines EFL students’ ability in answering the Structure and Written Expression section of a TOEFL prediction test. Using a descriptive quantitative approach, the participants were 10 seventh-semester students of the English Education Department at UMMY Solok in the 2023/2024 academic year. Data were collected through a 40-item TOEFL prediction test. The results indicate that students’ performance was categorized as poor in both sections. In the Structure section, the average number of correct answers was 5 (33%), while in the Written Expression section, the average was 10 (40%). The findings reveal that students experienced difficulties, particularly in identifying verb tenses. Therefore, it is recommended that students undertake more systematic preparation to improve their grammatical competence before taking the TOEFL test.